Implementasi Algoritma Distributed Color Selection untuk Mengatasi Collision Multi-reader pada Sistem RFID - Ridzhal Hachim Wahyunanto; Sabriansyah Rizqika Akbar; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Radio frequency Identification (RFID) is an automatic identification technology that transmits data via radio frequency electromagnetic ranging is applied to various fields, replacing the other automatic identification system. However, RFID has a fatal weakness, that is very vulnerable on collision data, that caused interference between signals the reader to each other. In this problem required an anti-collision algorithms to resolve the collision. in this study the algorithms used are Distributed Color Selection (DCS). DCS is anti-collision algorithms based Time Division Multiple Access (TDMA) that uses the specified time interval called timeslot. Each reader choose timeslot each and when the system began, the reader will only be active in accordance with selected timeslot. The system was tested using the RFID reader module MFRC522 13.56 MHz and RFID tags 13.56 MHz with the different variation number of readers and the total number of timeslot customized with number of readers. RFID is connected to the Arduino Uno microcontroller and the results are displayed on serial monitor Arduino IDE which then calculated the efficiency of identification works. The result of calculation and testing can be inferred, the highest efficiency when using 2 readers for identification without the use of algorithms is 40% while using DCS is 100% Results for used 3 readers without the algorithms was 10% while using DCS is 80%. As well as using 4 readers without algorithm is 0% while using DCS is 70%.